Of Slight, Spite, and Suspicion: The Treatment of India in E. M. Forster’s A Passage to India - Debashish Biswas; Samia Yesmin; Prakash Chandra Biswas (Women, Education, and Social Welfare, 2025)
This study analyzes E. M. Forster’s A Passage to India through the lens of colonial psychology, examining the intricate dynamics between the British colonizers and the Indian populace. The research focuses on the recurring themes of "slight," "spite," and "suspicion," highlighting how these attitudes manifest in the interactions between British and Indian characters. Through a detailed analysis of Forster's portrayal of colonial attitudes, this paper explores how the British perceive India through a lens of superiority, condescension, and distrust, reinforcing a racial hierarchy that permeates social, cultural, and religious domains. By interpreting these psychological underpinnings, the study reveals the lasting effects of colonialism on both the colonizers and the colonized, emphasizing how imperial ideologies obstruct genuine human connection. The research applies a qualitative approach, using textual analysis and postcolonial theory, with a particular focus on the symbolic use of space, language, and the Marabar Caves incident. This paper contributes to postcolonial scholarship by offering a critical re-evaluation of A Passage to India, focusing on the colonial mindset and its implications for cross-cultural relations.